2014
DOI: 10.1038/bjc.2014.174
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survivor characteristics in HER2-positive metastatic breast cancer from registHER

Abstract: Background:Data characterising long-term survivors (LTS) with human epidermal growth factor receptor 2 (HER2)–positive metastatic breast cancer (MBC) are limited. This analysis describes LTS using registHER observational study data.Methods:A latent class modelling (LCM) approach was used to identify distinct homogenous patient groups (or classes) based on progression-free survival (PFS), overall survival, and complete response. Demographics, clinicopathologic factors, first-line treatment patterns, and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 55 publications
(61 reference statements)
2
25
0
1
Order By: Relevance
“…As recently shown in the registHER study, a large multicenter, prospective cohort study in patients with HER2-positive metastatic breast cancer, both nonvisceral metastases (in particular, node and local sites) and hormone receptor positivity are factors associated with long-term survival [20].…”
Section: ©Alphamed Press 2015mentioning
confidence: 75%
“…As recently shown in the registHER study, a large multicenter, prospective cohort study in patients with HER2-positive metastatic breast cancer, both nonvisceral metastases (in particular, node and local sites) and hormone receptor positivity are factors associated with long-term survival [20].…”
Section: ©Alphamed Press 2015mentioning
confidence: 75%
“…Factors associated with longer OS included ER-or PR-positive disease, metastasis to bone only or bone plus breast or node/local sites, first-line trastuzumab use and first-line taxane use (20).…”
Section: Prognostic and Predictive Factors On Anti-her2 Treatmentmentioning
confidence: 99%
“…[4, 8] It has been recently reported that 25–30% of patients with HER2-positive MBC survived five or more years following treatment with HER2-targeted therapy. [9, 10]…”
Section: Introductionmentioning
confidence: 99%